2023
DOI: 10.1101/2023.05.09.539992
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulatory mechanisms in multiple vascular diseases locusLRP1involve repression by SNAIL and extracellular matrix remodeling

Abstract: Background: Genome-wide association studies (GWAS) implicate common genetic variations in the low-density lipoprotein receptor-related protein 1 locus (LRP1) in risk for multiple vascular diseases and traits. However, the underlying biological mechanisms are unknown. Methods: Fine mapping analyses included Bayesian colocalization to identify the most likely causal variant. Human induced pluripotent stem cells (iPSC) were genome-edited using CRISPR-Cas9 to delete or modify candidate enhancer regions, and genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…LRP1 is also involved in vascular calcium signaling by regulating smooth muscle cell contractility 38 . A recent study suggested that LRP1 expression is regulated by allele- specific mechanism of intronic rs11172113 located in an enhancer region through two transcription factors (MECP2 and SNAIL) 40 .…”
Section: Resultsmentioning
confidence: 99%
“…LRP1 is also involved in vascular calcium signaling by regulating smooth muscle cell contractility 38 . A recent study suggested that LRP1 expression is regulated by allele- specific mechanism of intronic rs11172113 located in an enhancer region through two transcription factors (MECP2 and SNAIL) 40 .…”
Section: Resultsmentioning
confidence: 99%